Computational study on water based hybrid photovoltaic systems with different absorber configurations - Jitendra Satpute; Gouri Ghongade; Jana Petrů; Srinidhi Campli; Sunita Yadav; PavanKumar Sonawane; Harish Venu; Muhammad Nasir Bashir; Manzoore Elahi M. Soudagar; Shylesha Channapattana (Scientific Reports)
Abstract The current study assesses several water-based PVT system thermal absorber configurations. The thermal absorber in PVT system plays a vital role in efficiency evaluation as it lowers PV temperature and collects heat energy. The current study aims to discover and analyze advanced thermal absorber design by comparing well-received spiral circular absorbers and non-cooled PV with proposed semi-circular thermal absorbers with varying flow configurations. The proposed thermal absorber maintains surface contact with PV panels and improves heat transfer thereby yielding better thermal and electrical efficiency. Simulated PVT systems have a constant water flow rate and solar radiation. The CFD-FLUENT software was preferred to evaluate the PVT system in steady-state conditions for the investigation. Under constant ambient and inlet water temperatures of 299 K, the PV temperatures at the surface, water discharge temperature, and pressure drop were measured. It was discovered that a thermal absorber could effectively lower PV surface temperature by cooling. A zigzag thermal absorber was the most efficient since it produced the highest water outlet temperature and lowest PV surface temperature while also slightly raising the pressure drop. In comparison with a non-cooled PV system, a zigzag thermal absorber PVT system yields 11.97% more electrical efficiency, with an addition of 76.75% thermal efficiency. It was also noticed that a conventional spiral circular PVT system provides 13.5% electrical efficiency and 54.8% thermal efficiency while an electrical efficiency of 13.61% and thermal efficiency is 76.75% was obtained from a zigzag thermal absorber PVT system. The zigzag thermal absorber PVT system had a high initial investment of INR 38809.00. It showed a simple payback of 4.63 years, a 28% return on investment with a promising 2.1 Debt Service Coverage Ratio. It is advisable to consider incorporating zigzag semi-circular PVT in the prospective improvements of the PVT system.